Electron-gated ion channels with amplification by NH3 inversion resonance - Ralston, Wilson P. (SciTech Publishing, 2005)
The following topics are dealt with: electron-gating model; sodium channel current; single electron two-site model; NH3 inversion resonance; two-site electron tunneling; displacement capacitance; amplified electron tunneling; Marcus inverted region; tunneling resistance; ion channel gating; electron gating model equations; potassium channel flux gating; charge immobilization; calcium channel oscillator model; electron-gated K3 channels; microwave thermal fluorescence spectroscopy; blue fluorescent protein; and first excited vibrational state.